Analysis of the use of potentially inappropriate medication in elderly hospitalized in an Intensive Care Unit in a large hospital in Recife (Research, Society and Development, 2022)
Aim: To analyze the use of potentially inappropriate drugs prescribed to the elderly in Intensive Care Units. Methodology: Observational, descriptive, cross-sectional and retrospective study. The study was carried out by analyzing the electronic medical records of patients over 60 years of age, using potentially inappropriate drugs in the elderly with action on the central nervous system. Clinical and sociodemographic data were collected, as well as data regarding the use of these drugs (active pharmaceutical ingredient, drug class, treatment time, clinical indication and adverse reactions). Results: The most prescribed therapeutic classes were benzodiazepines, antipsychotics and hypnotics. Among the uses, 7.6% had no clinical justification, and the other justifications included medication reconciliation, hyperactive delirium, weaning from sedation and insomnia as the most frequent. Adverse reactions such as lowered level of consciousness, daytime sleepiness, constipation, mental confusion, and others have been observed. The results obtained are in agreement with the expected results regarding the possibility of contributing to the discussion on the current scenario of the use of potentially inappropriate drugs for the elderly in Intensive Care Units and possible perspectives and therapeutic alternatives. Conclusion: It is important to emphasize the importance of monitoring the use of these drugs when their use is unavoidable, as well as avoiding or reducing their prescription, associating other therapies with lower risk, in view of the potential harmful effects of inappropriate drugs.